THE EFFECT OF REPEATED COMPACTION ON STARCH 1500 AS A FILLER-BINDER OF DIRECT COMPRESSION TABLET - Sri Sulihtyowati Soebagyo; Muliyadi . (Indonesian Journal of Pharmacy, 2001)
Poor flowability is the weakness of Starch 1500 as a filler-binder of direct compression tablet. Granulation by compaction is one of the ways to improve the flow ability as it produced larger granules. Compaction of Starch 1500 (once) produced granules having flowability, compressibility and compactibility better than the original Starch 1500 powder. These granules, eventually, yielded tablets having higher hardness, less friable and longer disintegration time than that of the original Starch 1500. On twice compaction of Starch 1500, however, produced more fluid granules than previous method but the compressibility and compactibility tended to decrease. These type of granules yielded tablets having lower hardness and friability but higher disintegration time, significantly. Key words: Starch 1500, granule, flowability, compressibility, tablet properties